A Qualitative Approach to Women’s Perspectives on Exercise in Iran - Kalani, Zohreh (Int J Community Based Nurs Midwifery, 2018)
BACKGROUND: It is believed that women of all ages do less physical activities compared to men. The development of interventional projects for increasing the women’s participation in physical activity needs the recognition of resources and exploration of women’s perspectives on exercise in their lives in the Iranian culture and context. METHODS: This qualitative study was conducted in an urban area of Iran on 46 women attending healthcare centers, volunteer health care providers, university students, sportswomen and one of the officials of the provincial women’s sports. This study was done from April 2015 to June 2016. Four focus group discussions and one in depth semi-structured interview was conducted. A qualitative conventional content analysis approach was used for data analysis. RESULTS: Four categories were developed as follows: ‘preferences’, ‘planning’, ‘motivators’ and ‘inhibitors’. Preferences had three distinct subcategories: preferences to do exercise in specific settings, specific exercise and group exercise. The family role, exercise as one part of daily routines, and exercise as a habit were subcategories of planning. Motivators were physical, emotional and social benefits; physician advice and encouragement; being alarmed; and championship. The inhibitors of doing exercise were various: gender issues, economical and costs issues, geographical access, making excuses, cultural infrastructures, shortage of sports experts, fears, concerns and misconceptions, inappropriate facilities and inadequate administrative cooperation and official barriers. CONCLUSION: The findings showed that the women were sensitive to and interested in doing exercise. However, barriers to exercise were multiple and complex. Nursing interventions are required to increase the individuals’ awareness of misconceptions and also develop strategic programs for improving exercise among women.